1990
DOI: 10.1143/jjap.29.l438
|View full text |Cite
|
Sign up to set email alerts
|

XPS Studies of 80 K-Phase Bi-Sr-Ca-Cu-O Single Crystals

Abstract: The XPS (X-ray photoelectron spectroscopy) measurements of the 80 K-phase Bi-Sr-Ca-Cu-O single crystals were carried out on surfaces obtained by cleaving in vacuum, by cleaving in air and heating in vacuum, and by Ar+-sputter etching of the air-cleaved-and-heated surface. The chemical bond natures of all the constituent elements from the air-cleaved-and-heated surface are approximately equal to those from the vacuum-cleaved surface. Sr and Ca from the sputtered surface are more oxidized than those from the vac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1991
1991
2015
2015

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…It was reported that the XPS peak positions of Sr 3d shifted to the higher-energy side upon oxidation. 25,26,28 This is due to the greater electronegativity of oxygen. So in our case, Sr 3d 3/2 can be further deconvoluted into Sr-O (3d 3/2 ) and Sr-N (3d 3/2 ) at B136.12 and B135.13 eV, respectively, and Sr 3d 5/2 into Sr-O (3d 5/2 ) and Sr-N (3d 5/2 ) at B134.32 and B133.31 eV, respectively.…”
Section: Xps Analysismentioning
confidence: 99%
“…It was reported that the XPS peak positions of Sr 3d shifted to the higher-energy side upon oxidation. 25,26,28 This is due to the greater electronegativity of oxygen. So in our case, Sr 3d 3/2 can be further deconvoluted into Sr-O (3d 3/2 ) and Sr-N (3d 3/2 ) at B136.12 and B135.13 eV, respectively, and Sr 3d 5/2 into Sr-O (3d 5/2 ) and Sr-N (3d 5/2 ) at B134.32 and B133.31 eV, respectively.…”
Section: Xps Analysismentioning
confidence: 99%